Innovation, institutional ownership and financial constraints - Jan Philip Schain; Joel Stiebale (Empirical Economics, 2020)
We analyze the relationship between institutional investors, innovation and financing constraints. Using the same dataset as Aghion et al. (Am Econ Rev 103(1):277–304, 2013), we find that the effect of institutional ownership on innovation is concentrated in industries with high dependence on external finance and among firms which are a priori likely to be financially constrained. The complementarity between institutional ownership and competition, predicted by the original paper's theory where institutional investors increase innovation through reducing career risks, disappears once this heterogeneity is taken into account. We also provide evidence that the sensitivity of R&D investment to internal funds decreases with institutional ownership.
Keywords: G23; G32; L25; M10; O31; O34; 330; G23; G32; L25; M10; O31; O34